Data Science in the Public Interest : Improving Government Performance in the Workforce - Hawley, Joshua D. (Book collections on Project MUSE., 2020)
"This book is about how new and underutilized types of big data sources can inform public policy decisions related to workforce development. Hawley describes how government is currently using data to inform decisions about the workforce at the state and local levels. He then moves beyond standardized performance metrics designed to serve federal agency requirements and discusses how government can improve data gathering and analysis to provide better, up-to-date information for government decision making"--